Numerical simulation of nanofluid forced convection heat transfer - Mohd Taufidd, Tawang (2010)
The thesis deals with the numerical simulation of nanofluid forced convection heat transfer under the turbulent flow with different volume concentrations. The objective of this thesis is to study the heat transfer coefficient of nanofluid at various volume concentrations and Reynolds number using Computational Fluid Dynamic (CFD) software. This thesis describes the CFD analysis techniques to predict the heat transfer coefficient using FLUENT software. Aluminum Oxide, Al2O3/Water with 0.02%, 0.1% and 0.5% of volume concentration were studied in this thesis which commonly available nanofluid in market. The structural three-dimensional solid modelling of plain pipe tube was developed using the computer aided-drawing software, SolidWorks. The strategy of validation of CFD model was developed by comparing the result from water simulation with the available equation in the study of forced convection heat transfer. The CFD analysis was then performed using FLUENT with nanofluid as the working fluid. The CFD model of components was analyzed using the pressure based solver and k-epsilon viscous model. Finally, the bulk temperature and wall temperature of the working fluid obtained from the simulation are used to calculate the heat transfer coefficient of the fluid. From the result, it is observed that the heat transfer coefficient of base fluid, water is increased about 20% in the presence of nanoparticles when Reynolds number and volume concentration are increase. But, increase in heat transfer coefficient by increasing volume concentration of nanofluid is valid when Reynolds number below 10,000. Results obtained from simulation were then compared with the experiment and it is observed that a close agreement between simulation and experiment is achieved. Both simulation and experiment results concluded that the heat transfer coenfficient increase when nanofluid is used as the working fluid. These results are significant to improve today cooling fluid in the way of increasing the heat transfer coefficient.